Leveraging Game-Based Learning in Mathematics Education: Enhancing Engagement and Efficiency Through Management Information Systems - Mema, Besjana; Basholli, Albina; Sheikhaleslami, Zahra (Karshi Multidisciplinary International Scientific Journal, 2024)
The integration of game-based learning (GBL) into mathematics education has emerged as a promising approach to enhance student engagement and understanding of complex concepts. Simultaneously, the use of management information systems (MIS) offers an innovative framework for monitoring and optimizing the implementation of such educational methods. This study explores the intersection of GBL and MIS, focusing on their combined potential to improve teaching and learning outcomes in mathematics. By leveraging MIS, educators can collect and analyze data on student performance, customize learning experiences, and address individual needs effectively. The article also discusses challenges in integrating these technologies and provides recommendations for further development. This research highlights the transformative potential of combining GBL and MIS in fostering a more interactive and data-driven approach to mathematics education.